New data on the distribution of the rare myxomycete Tubifera dudkae (Reticulariaceae) in the context of the contribution of citizen science to the biodiversity monitoring (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
Tubifera dudkae is a rare species, described in 2011. Literature data on its distribution are limited to Ukraine (typical locality), France and Russia. At the same time, the species has a recognizable morphology and bright color of fruiting bodies, images of which can often be found on web resources related to citizen (amateur) science. The aim of this study was to accumulate all available data on findings of T. dudkae, collected by amateur activists and to combine them with information collected by professional mycologists. The study was based on specimens stored in the CWP Scientific Herbarium, as well as illustrative materials, that can be identified to the level of the species, distributed in various online sources (GBIF, iNaturalist, UrkBIN) or sent to the author by professional amateurs. A search for information about findings of T. dudkae in publicly available sources showed the presence of references to the species, but mostly with incorrect identifications. At the same time, we have found high-quality images of T. dudkae on resources like MycoWeb, www.dziedava.lv and in the Slime Mold Identification & Appreciation group on Facebook. A total of 23 observations from 20 localities of T. dudkae were identified, 16 of which are new. Citizen scientists provided first data about distribution of T. dudkae in Netherlands, Latvia and Sweden. According to the data obtained, T. dudkae is distributed in Europe and North-West Asia in a fairly wide range of climatic conditions, from the Mediterranean (Crimea, Cote d'Azur) to the zone of mixed forests (southern Scandinavia, Moscow region). Substrate preferences of the species are also relatively broad: it occurs on dead wood of oak, pine, spruce, bare or covered with mosses and lichens, and even on fallen conifer needles. Thus, T. dudkae gives the impression of a species with a wide range of ecological tolerance. The analyzed data indicate that it is distributed in a Euro-Siberian area.
Keywords: Eumycetozoa, citizen science, cosmopolitanism, species distribution, social networks, terrestrial protists.